Mismatches between the current marine Natura 2000 network and seabird distributions call for enhanced protected areas off metropolitan France - Timothée Poupart; Thibaut de Bettignies; Matthieu Authier; Nicola Baccetti; Luca Börger; Iker Castège; Jacopo G. Cecere; Nicolas Courbin; Jamie Darby; Karine Delord; Ghislain Doremus; Hayley A. Douglas; et al. (Marine Policy, 2025)

I sink therefore I am: 20 years of tagging small cetacean carcasses in the North-East Atlantic for bycatch estimation - Hélène Peltier; Matthieu Authier; Willy Dabin; Pierre Daniel; Cécile Dars; Fabien Demaret; Eleonore Meheust; Vincent Ridoux; Jérôme Spitz; Olivier Van Canneyt (Journal for Nature Conservation, 2025)

Going digital: challenges in monitoring marine megafauna when comparing results from visual and digital aerial surveys - Maud Quéroué; Matthieu Authier; Aurélien Besnard; Karine Heerah (Frontiers in Marine Science, 2024)
Since the first plans to develop offshore wind farms (OWFs), concerns have been raised about the impacts on marine megafauna. Today, it is required to assess these impacts over the whole lifecycle of the OWF. Before construction, initial assessments are often conducted by visual surveys, but subsequent monitoring over the lifecycle of the OWF has to be digital due to safety requirements, leading to challenges in data comparability. The aim of this study was to attempt to establish generalizable intercalibration factors for this transition between visual and digital monitoring methods. To this end, intercalibration surveys were conducted at five different sites and at different times of the year within a site, using both visual monitoring at low-altitude and digital monitoring at both low and high altitudes. We tested the potential for intercalibration of the results based on the ratio of abundance estimated from data collected by the different methods. We explored factors such as the species under study and site-specific conditions that may influence intercalibration. We computed more than 100 intercalibration factors and found that, on average, abundance estimates from digital methods were higher than those from visual methods and that flight altitude for digital monitoring did not significantly influence abundance estimates. Aside from divergent abundance estimates depending on monitoring method, the findings also revealed significant heterogeneity, only one-third of which was explained by contextual factors such as taxonomy or the sea conditions. This outcome presents a pessimistic outlook on the prospect for the intercalibration of results between an initial assessment carried out with visual observations and subsequent monitoring with digital methods after OWF construction and until decommissioning. The high heterogeneity prevents seamless transferability of intercalibration factors and highlights the importance of local context.

Identification of static netters fishing trajectories with high resolution data and their evolution in the Bay of Biscay since 2015: Potential implications for short-beaked common dolphin bycatch - Jade Paillé; Corentin Vignard; Matthieu Authier; Emeric Bidenbach; Camille Deslias; Stéphanie Tachoires; Hélène Peltier (Fisheries Research, 2024)

Using fusion effects to decrease uncertainty in distance sampling models when collating data from different surveys - Floriane Plard; Hélder Araújo; Amaia Astarloa; Maite Louzao; Camilo Saavedra; José Antonio Vazquez Bonales; Graham John Pierce; Matthieu Authier (Marine Mammal Science, 2024)
Estimates of population abundance are required to study the impacts of human activities on populations and assess their conservation status. Despite considerable effort to improve data collection, uncertainty around estimates of cetacean densities can remain large. A fundamental concept underlying distance sampling is the detection function. Here we focus on reducing the uncertainty in the estimation of detection function parameters in analyses combining data sets from multiple surveys, with known effects on the precision of density estimates. We developed detection functions using infinite mixture models that can be applied on data collating multiple species and/or surveys. These models enable automatic clustering by fusing the species and surveys with similar detection functions. We present a simulation analysis of a multisurvey data set in a Bayesian framework where we demonstrated that distance sampling models including fusion effects showed lower uncertainty than classical distance sampling models. We illustrated the benefits of this new model using data of line transect surveys from the Bay of Biscay and Iberian Coast. Future estimates of abundance using conventional distance sampling models on large multispecies surveys or on data sets combining multiple surveys could benefit from this new model to provide more precise density estimates.

Addressing temporal trends in survivorship from cross-sectional sampling designs: A modelling framework with applications for megafauna conservation - Etienne Rouby; Matthieu Authier; Emmanuelle Cam; Ursula Siebert; Floriane Plard (Ecological Modelling, 2024)

A negative trend in abundance and an exceeded mortality limit call for conservation action for the Vulnerable Belt Sea harbour porpoise population - Kylie Owen; Anita Gilles; Matthieu Authier; Julia Carlström; Mathieu Genu; Line Anker Kyhn; Dominik A. Nachtsheim; Nadya C. Ramírez-Martínez; Ursula Siebert; Martin Sköld; Jonas Teilmann; Bianca Unger; et al. (Frontiers in Marine Science, 2024)
The management and conservation of biodiversity relies on information on both the abundance of species and the potential impact of threats. Globally, one of the largest threats towards marine biodiversity is bycatch in fisheries. Under the Marine Strategy Framework Directive (MSFD), EU Member States are required to assess the status of species, such as the harbour porpoise ( Phocoena phocoena ), in relation to their abundance and mortality due to bycatch every six years. The Vulnerable (HELCOM) Belt Sea population of harbour porpoise has been surveyed to determine its abundance six times using dedicated aerial or ship-based line-transect distance sampling surveys. Here, we estimated the first trend in population abundance over an 18 year period (2005-2022). Using the most recent abundance estimate, we computed a mortality limit applying the modified Potential Biological Removal (mPBR) method based on the regionally agreed conservation objective to restore or maintain 80% of carrying capacity over 100 years with an 80% probability. Over the past 18 years there has been a strong negative trend (-2.7% p.a.; 95% CI: -4.1%; + 1.3%) in abundance, with a 90.5% probability. The mortality limit was estimated to be 24 animals, which the current bycatch estimates (~900 porpoises/year from the commercial Danish and Swedish set net fishery fleets, with no data from Germany and other fishery types) exceed by far. The frequency and quality of data available on abundance for this population are higher than those available for the majority of marine species. Given the observed population decline and likely unsustainable levels of bycatch, the results presented here provide a strong basis to make informed, evidence-based management decisions for action for this population. Such action is needed urgently, before the dire situation of other porpoise species and populations around the globe is repeated.

Prospective modelling of operational offshore wind farms on the distribution of marine megafauna in the southern North Sea - Auriane Virgili; Sophie Laran; Matthieu Authier; Ghislain Dorémus; Olivier Van Canneyt; Jérôme Spitz (Frontiers in Marine Science, 2024)
Intense development of Offshore Wind Farms (OWFs) has occurred in the North Sea with several more farms planned for the near future. These OWFs pose a threat to marine megafauna stressing the need to mitigate the impact of human activities. To help mitigate impacts, the Before After Gradient (BAG) design was proposed. We explored the use of the BAG method on megafauna sightings recorded at different distances from OWFs in the southern North Sea. We predicted intra-annual variability in species distribution, then correlated species distribution with the presence of operational OWFs and investigated the potential impact the operation of prospective OWFs may have on species distribution. Four patterns of intra-annual variability were predicted: species most abundant in spring, in winter, in both spring and winter, or all year round. We recommend that future OWF constructions be planned in summer and early fall to minimise impact on cetaceans and that offshore areas off northern France and Belgium be avoided to minimise impact on seabirds. Our prospective analysis predicted a decreased density for most species with the operation of prospective OWFs. Prospective approaches, using e.g. a BAG design, are paramount to inform species conservation as they can forecast the likely responses of megafauna to anthropogenic disturbances.

Estimation of total population size of southern elephant seals (Mirounga leonina) on Kerguelen and Crozet Archipelagos using very high-resolution satellite imagery - Joris Laborie; Matthieu Authier; Adrien Chaigne; Karine Delord; Henri Weimerskirch; Christophe Guinet (Frontiers in Marine Science, 2023)
Southern elephant seals ( Mirounga leonina ) play a pivotal role in the Southern Ocean as wide-ranging marine predators and major prey consumers within Southern Ocean marine ecosystems. Due to their circumpolar distribution and the remoteness of their habitat, large uncertainties remain about their total population sizes. This is especially true for elephant seal populations in the French Southern Territories in the southern Indian Ocean (i.e. Crozet and Kerguelen Archipelagos) as many breeding sites are inaccessible for ground censuses. Here, we present a simple and efficient approach for estimating the total elephant seal populations of the Kerguelen and Crozet Archipelagos by using very high-resolution satellite imagery (<1m resolution). Twenty-eight satellite images taken during the breeding season to count female elephant seals in inaccessible areas were used and complemented the traditional annual ground counts in accessible areas. For Kerguelen Island sectors likely to host colonies and where no satellite images were available for the breeding season, a statistical predictive model was built to estimate the most likely number of breeding females to be present on a given beach according to its physiographic characteristics. Our results show the reliability of using very high-resolution satellite images, a relatively low-cost platform, to count pinniped populations and provide the first estimation of the total southern elephant seal population for both the Kerguelen 347,995 (s e = 4,950) and Crozet 13,065 (s e = 169) Archipelagos. The combined total represents over 35% of the global elephant seal population with the Kerguelen stock being numerically equivalent to the South Georgia stock. In addition, we re-examined the population trends since the last mid-century for Kerguelen and over the last five decades for Crozet. The demographic trends of the southern Indian Ocean populations show marked growth over the last decade (5.1% and 1.6% annual growth rate for Crozet and Kerguelen respectively), particularly on Crozet where the elephant seal population has more than tripled.

Temporal correlations among demographic parameters are ubiquitous but highly variable across species - Rémi Fay; Sandra Hamel; Martijn van de Pol; Jean‐Michel Gaillard; Nigel G. Yoccoz; Paul Acker; Matthieu Authier; Benjamin Larue; Christie Le Coeur; Kaitlin R. Macdonald; Alex Nicol‐Harper; Christophe Barbraud; et al. (Ecology Letters, 2022)
Temporal correlations among demographic parameters can strongly influence population dynamics. Our empirical knowledge, however, is very limited regarding the direction and the magnitude of these correlations and how they vary among demographic parameters and species’ life histories. Here, we use long‐term demographic data from 15 bird and mammal species with contrasting pace of life to quantify correlation patterns among five key demographic parameters: juvenile and adult survival, reproductive probability, reproductive success and productivity. Correlations among demographic parameters were ubiquitous, more frequently positive than negative, but strongly differed across species. Correlations did not markedly change along the slow‐fast continuum of life histories, suggesting that they were more strongly driven by ecological than evolutionary factors. As positive temporal demographic correlations decrease the mean of the long‐run population growth rate, the common practice of ignoring temporal correlations in population models could lead to the underestimation of extinction risks in most species.

Estimating Bycatch From Non-representative Samples (II): A Case Study of Pair Trawlers and Common Dolphins in the Bay of Biscay - Etienne Rouby; Laurent Dubroca; Thomas Cloâtre; Sebastien Demanèche; Mathieu Genu; Kelly Macleod; Hélène Peltier; Vincent Ridoux; Matthieu Authier (Frontiers in Marine Science, 2022)
Marine megafauna plays an important functional role in marine ecosystems as top predators but are threatened by a wide range of anthropogenic activities. Bycatch, the incidental capture of non-targeted species in commercial and recreational fisheries, is of particular concern for small cetacean species, such as dolphins and porpoises. In the North-East Atlantic, common dolphin ( Delphinus delphis , Linné 1758) bycatch has been increasing and associated with large numbers of animals stranding during winter on the French Atlantic seashore since at least 2017. However, uncertainties around the true magnitude of common dolphin bycatch and the fisheries involved have led to delays in the implementation of mitigation measures. Current data collection on dolphin bycatch in France is with non-dedicated observers deployed on vessels for the purpose of national fisheries sampling programmes. These data cannot be assumed representative of the whole fisheries' bycatch events. This feature makes it difficult to use classic ratio estimators since they require a truly randomised sample of the fishery by dedicated observers. We applied a newly developed approach, regularised multilevel regression with post-stratification, to estimate total bycatch from unrepresentative samples and total fishing effort. The latter is needed for post-stratification and the former is analysed in a Bayesian framework with multilevel regression to regularise and better predict bycatch risk. We estimated the number of bycaught dolphins for each week and 10 International Council for the Exploration of the Sea (ICES) divisions from 2004 to 2020 by estimating jointly bycatch risk, haul duration, and the number of hauls per days at sea (DaS). Bycatch risk in pair trawlers flying the French flag was the highest in winter 2017 and 2019 and was associated with the longest haul durations. ICES divisions 8.a and 8.b (shelf part of the Bay of Biscay) were estimated to have the highest common dolphin bycatch. Our results were consistent with independent estimates of common dolphin bycatch from strandings. Our method show cases how non-representative observer data can nevertheless be analysed to estimate fishing duration, bycatch risk and, ultimately, the number of bycaught dolphins. These weekly-estimates improve upon current knowledge of the nature of common dolphin bycatch and can be used to inform management and policy decisions at a finer spatio-temporal scale than has been possible to date. Our results suggest that limiting haul duration, especially in winter, could serve as an effective mitigation strategy.

Evaluating Strategies for Managing Anthropogenic Mortality on Marine Mammals: An R Implementation With the Package RLA - Mathieu Genu; Anita Gilles; Philip S. Hammond; Kelly Macleod; Jade Paillé; Iosu Paradinas; Sophie Smout; Arliss J. Winship; Matthieu Authier (Frontiers in Marine Science, 2021)
Bycatch, the undesirable and non-intentional catch of non-target species in marine fisheries, is one of the main causes of mortality of marine mammals worldwide. When quantitative conservation objectives and management goals are clearly defined, computer-based procedures can be used to explore likely population dynamics under different management scenarios and estimate the levels of anthropogenic removals, including bycatch, that marine mammal populations may withstand. Two control rules for setting removal limits are the Potential Biological Removal (PBR) established under the US Marine Mammal Protection Act and the Removals Limit Algorithm (RLA) inspired from the Catch Limit Algorithm (CLA) developed under the Revised Management Procedure of the International Whaling Commission. The PBR and RLA control rules were tested in a Management Strategy Evaluation (MSE) framework. A key feature of PBR and RLA is to ensure conservation objectives are met in the face of the multiple uncertainties or biases that plague real-world data on marine mammals. We built a package named RLA in the R software to carry out MSE of control rules to set removal limits in marine mammal conservation. The package functionalities are illustrated by two case studies carried out under the auspices of the Oslo and Paris convention (OSPAR) (the Convention for the Protection of the Marine Environment of the North-East Atlantic) Marine Mammal Expert Group (OMMEG) in the context of the EU Marine Strategy Framework Directive. The first case study sought to tune the PBR control rule to the conservation objective of restoring, with a probability of 0.8, a cetacean population to 80% of carrying capacity after 100 years. The second case study sought to further develop a RLA to set removals limit on harbor porpoises in the North Sea with the same conservation objective as in the first case study. Estimation of the removals limit under the RLA control rule was carried out within the Bayesian paradigm. Outputs from the functions implemented in the package RLA allows the assessment of user-defined performance metrics, such as time to reach a given fraction of carrying capacity under a given level of removals compared to the time needed given no removals.

Using single visits into integrated occupancy models to make the most of existing monitoring programs - Valentin Lauret; Hélène Labach; Matthieu Authier; Olivier Gimenez (Ecology, 2021)
A major challenge in statistical ecology consists of integrating knowledge from different data sets to produce robust ecological indicators. To estimate species distribution, occupancy models are a flexible framework that can accommodate several data sets obtained from different sampling methods. However, repeating visits at sampling sites is a prerequisite for using standard occupancy models. Occupancy models were recently developed to analyze detection/non‐detection data collected during a single visit. To date, single‐visit occupancy models have never been used to integrate several different data sets. Here, we showcase an approach that combines two data sets into an integrated single‐visit occupancy model. As a case study, we estimated the distribution of common bottlenose dolphin ( Tursiops truncatus ) over the northwestern Mediterranean Sea by combining 24,624 km of aerial surveys and 21,464 km of at‐sea monitoring. We compared the outputs of single‐ vs. repeated‐visit occupancy models into integrated occupancy models. Integrated models allowed a better sampling coverage of the targeted population, which provided a better precision for occupancy estimates than occupancy models using data sets in isolation. Overall, single‐ and repeated‐visit integrated occupancy models produced similar inference about the distribution of bottlenose dolphins. We suggest that single‐visit occupancy models open promising perspectives for the use of existing ecological data sets.

Estimating Cetacean Bycatch From Non-representative Samples (I): A Simulation Study With Regularized Multilevel Regression and Post-stratification - Matthieu Authier; Etienne Rouby; Kelly Macleod (Frontiers in Marine Science, 2021)
Bycatch, the non-intentional capture or killing of non-target species in commercial or recreational fisheries, is a world wide threat to protected, endangered or threatened species (PETS) of marine megafauna. Obtaining accurate bycatch estimates of PETS is challenging: the only data available may come from non-dedicated schemes, and may not be representative of the whole fisheries effort. We investigated, with simulated data, a model-based approach for estimating PETS bycatch from non-representative samples. We leveraged recent development in the statistical analysis of surveys, namely regularized multilevel regression with post-stratification, to infer total bycatch under realistic scenarios of data sampling such as under-sampling or over-sampling when PETS bycatch risk is high. Post-stratification is a survey technique to re-align the sample with the population and addresses the problem of non-representative samples. Post-stratification requires to sub-divide a population of interest into potentially hundreds of cells corresponding to the cross-classification of important attributes. Multilevel regression accommodate this data structure, and the statistical technique of regularization can be used to predict for each of these hundreds of cells. We illustrated these statistical ideas by modeling bycatch risk for each week within a year with as few as a handful of observed PETS bycatch events. The model-based approach led to improvements, under mild assumptions, both in terms of accuracy and precision of estimates and was more robust to non-representative samples compared to more design-based methods currently in use. In our simulations, there was no detrimental effects of using the model-based even when sampling was representative. Estimating PETS bycatch ideally requires dedicated observer schemes and adequate coverage of fisheries effort. We showed how a model-based approach combining sparse data typical of PETS bycatch and recent methodological developments can help when both dedicated observer schemes and adequate coverage are challenging to implement.

Corrigendum: In the Wrong Place at the Wrong Time: Identifying Spatiotemporal Co-occurrence of Bycaught Common Dolphins and Fisheries in the Bay of Biscay (NE Atlantic) From 2010 to 2019 - Helene Peltier; Matthieu Authier; Florence Caurant; Willy Dabin; Pierre Daniel; Cecile Dars; Fabien Demaret; Eleonore Meheust; Olivier Van Canneyt; Jerome Spitz; Vincent Ridoux (Frontiers in Marine Science, 2021)

In the Wrong Place at the Wrong Time: Identifying Spatiotemporal Co-occurrence of Bycaught Common Dolphins and Fisheries in the Bay of Biscay (NE Atlantic) From 2010 to 2019 - Helene Peltier; Matthieu Authier; Florence Caurant; Willy Dabin; Pierre Daniel; Cecile Dars; Fabien Demaret; Eleonore Meheust; Olivier Van Canneyt; Jerome Spitz; Vincent Ridoux (Frontiers in Marine Science, 2021)
The first Unusual Mortality Event (UME) related to fishing activity along the Atlantic coast recorded by the French Stranding Network was in 1989: 697 small delphinids, mostly common dolphins, washed ashore, most of them with evidence of having been bycaught. Since then, UMEs of common dolphins have been observed nearly every year in the Bay of Biscay; unprecedented records were broken every year since 2016. The low and unequally distributed observation efforts aboard fishing vessels in the Bay of Biscay, as well as the lack of data on foreign fisheries necessitated the use of complementary data (such as stranding data) to elucidate the involvement of fisheries in dolphin bycatch. The aim of this work was to identify positive spatial and temporal correlations between the likely origins of bycaught stranded common dolphins (estimated from a mechanistic drift model) and fishing effort statistics inferred from Vessel Monitoring System (VMS) data on vessels >12 m long. Fisheries whose effort correlated positively with dolphin mortality areas after 2016 included French midwater trawlers, French Danish seiners, French gillnetters, French trammel netters, Spanish bottom trawlers, and Spanish gillnetters. For the French fleet only, logbook declarations, sales, and surveys carried out by Ifremer were integrated into fishing effort data. Six fleets were active in common dolphin bycatch areas at least twice between 2016 and 2019: gillnetters fishing hake, trammel netters fishing anglerfish, bottom pair trawlers fishing hake, midwater pair trawlers fishing sea bass and hake, and Danish seiners fishing whiting. Except for changes in hake landings in some fisheries, there were no notable changes in total fishing effort practice (gear or target species) based on the data required by the ICES and Council of the European Union that could explain the large increase in stranded common dolphins recorded along the French Atlantic coast after 2016. Small scale or unrecorded changes could have modified interactions between common dolphins and fisheries, but could not be detected through mandatory data-calls. The recent increase in strandings of bycaught common dolphins could have been caused by changes in their distribution and/or ecology, or changes in fishery practices that were undetectable through available data.

Combining multiple visual surveys to model the habitat of deep‐diving cetaceans at the basin scale - Auriane Virgili; Matthieu Authier; Oliver Boisseau; Ana Cañadas; Diane Claridge; Tim Cole; Peter Corkeron; Ghislain Dorémus; Léa David; Nathalie Di‐Méglio; Charlotte Dunn; Tim E. Dunn; et al. (Global Ecology and Biogeography, 2019)
Aim Deep‐diving cetaceans are oceanic species exposed to multiple anthropogenic pressures including high intensity underwater noise, and knowledge of their distribution is crucial to manage their conservation. Due to intrinsic low densities, wide distribution ranges and limited presence at the sea surface, these species are rarely sighted. Pooling data from multiple visual surveys sharing a common line‐transect methodology can increase sightings but requires accounting for heterogeneity in protocols and platforms. Location North Atlantic Ocean and Mediterranean Sea. Time period 1998 to 2015. Major taxa Ziphiidae; Physeteriidae; Kogiidae. Methods About 1,240,000 km of pooled effort provided 630 sightings of ziphiids, 836 of physeteriids and 106 of kogiids. For each taxon, we built a hierarchical model to estimate the effective strip width depending on observation conditions and survey types. We then modelled relative densities in a generalized additive modelling framework. Geographical predictions were limited to interpolations identified with a gap analysis of environmental space coverage. Results Deeper areas of the North Atlantic gyre were mostly environmental extrapolation in the predictions, thereby highlighting gaps in sampling across the different surveys. For the three species groups, the highest relative densities were predicted along continental slopes, particularly in the western North Atlantic Ocean where the Gulf Stream creates dynamic frontal zones and eddies. Main conclusions Pooling a large number of surveys provided the first basin‐wide models of distribution for deep‐diving cetaceans, including several data‐deficient taxa, across the North Atlantic Ocean and the Mediterranean Sea. These models can help the conservation of elusive and poorly known marine megafauna.

Population response of an apex Antarctic consumer to its prey and climate fluctuations - Nathan Pacoureau; Matthieu Authier; Karine Delord; Christophe Barbraud (Oecologia, 2019)

A Comprehensive Survey of Pelagic Megafauna: Their Distribution, Densities, and Taxonomic Richness in the Tropical Southwest Indian Ocean - Sophie Laran; Matthieu Authier; Olivier Van Canneyt; Ghislain Dorémus; Pierre Watremez; Vincent Ridoux (Frontiers in Marine Science, 2017)

Irreplaceable area extends marine conservation hotspot off Tunisia: insights from GPS-tracking Scopoli’s shearwaters from the largest seabird colony in the Mediterranean - David Grémillet; Clara Péron; Jean-Baptiste Pons; Ridha Ouni; Matthieu Authier; Mathieu Thévenet; Jérôme Fort (Marine Biology, 2014)

How much are stranding records affected by variation in reporting rates? A case study of small delphinids in the Bay of Biscay - Matthieu Authier; Hélène Peltier; Ghislain Dorémus; Willy Dabin; Olivier Van Canneyt; Vincent Ridoux (Biodiversity and Conservation, 2014)

Shift in foraging grounds and diet broadening during ontogeny in southern elephant seals from Kerguelen Islands - Adrien Chaigne; Matthieu Authier; Pierre Richard; Yves Cherel; Christophe Guinet (Marine Biology, 2013)

Evidence for an age‐dependent influence of environmental variations on a long‐lived seabird's life‐history traits - Deborah Pardo; Christophe Barbraud; Matthieu Authier; Henri Weimerskirch (Ecology, 2013)
Theoretical and empirical studies have highlighted the effects of age on several life‐history traits in wild populations. There is also increasing evidence for environmental effects on their demographic traits. However, quantifying how individuals differentially respond to environmental variations according to their age remains a challenge in ecology. In a population of Black‐browed Albatrosses monitored during 43 years, we analyzed how life‐history traits varied according to age, and whether individuals of different ages responded in different ways to environmental conditions. To do so, we: (1) examined how age affected seven life‐history traits, (2) investigated differences in temporal variance of demographic traits between age classes, and (3) tested for age‐dependent effects of climate and fisheries covariates on demographic traits. Overall, there was a tendency for traits to improve during the first years of life (5–10 years), to peak and remain stable at middle age (10–30 years), and decline at old ages. At young ages, survival and reproductive parameters increased, except offspring body condition at fledging, suggesting that younger parents had already acquired good foraging capacities. However, they suffered from inexperience in breeding as suggested by their higher breeding failures during incubation. There was evidence for reproductive and actuarial senescence. In particular, breeding success and offspring body condition declined abruptly, suggesting altered foraging capacities of old individuals. Middle‐aged individuals had the lowest temporal variance of demographic traits. Although this is predicted by the theory of environmental canalization, it could also results from a higher susceptibility of young and old birds due to their respective inexperience and senescence. The highest temporal variances were found in old individuals. Survival was significantly influenced by sea surface temperatures in the foraging zone of this albatross population during breeding. During warm events survival of young and old individuals improved, whereas a decrease was observed for middle‐aged individuals. Presumably, during cold years with poor environmental conditions, young and old breeding birds may suffer more from intraspecific competition for resources than middle‐aged individuals. This study showed that age, known as a major factor structuring demography in long‐lived species, can also potentially influence the response of populations to global change.

Population trends of female Elephant Seals breeding on the Courbet Peninsula, îles Kerguelen - Matthieu Authier; Karine Delord; Christophe Guinet (Polar Biology, 2011)

Interdecadal changes in at‐sea distribution and abundance of subantarctic seabirds along a latitudinal gradient in the Southern Indian Ocean - CLARA PÉRON; MATTHIEU AUTHIER; CHRISTOPHE BARBRAUD; KARINE DELORD; DOMINIQUE BESSON; HENRI WEIMERSKIRCH (Global Change Biology, 2010)
Long‐term demographic studies have recently shown that global climate change together with increasing direct impacts of human activities, such as fisheries, are affecting the population dynamics of marine top predators. However, the effects of these factors on species distribution and abundance at sea are still poorly understood, particularly in marine ecosystems of the southern hemisphere. Using a unique long‐term data set of at‐sea observations, we tested for interdecadal (1980s vs. 2000s) changes in summer abundance and distribution of 12 species of Albatrosses and Petrels along a 30° latitudinal gradient between tropical and Antarctic waters of the southern Indian Ocean. There were contrasting effects of climate change on subantarctic seabird distribution and abundance at sea. While subtropical waters showed the highest rate of warming, the species that visited this water mass showed the greatest changes in distribution and abundance. The abundance of Wandering Albatrosses ( Diomedea exulans ), White‐chinned Petrels ( Procellaria aequinoctialis ) and Giant Petrels ( Macronectes sp.) declined markedly, whereas the other species showed contrasting trends or did not change. With the exception of the White‐chinned Petrel, these decreases were at least partly related to regional increase in sea surface temperature. The southward shift of Wandering Albatross and Prions ( Pachyptila spp.) distributions could be ascribed to species redistribution or decrease in abundance due to warming of the subtropical waters. Surprisingly, White‐chinned Petrel distribution shifted northward, suggesting more complex mechanisms. This study is the first to document a shift in species range in the Southern Ocean related to climate change and contrasting abundance changes. It suggests that some species might experience more severe impacts from climate change depending on the water masses they visit. As climate changes are predicted to continue in the next decades, understanding species responses to climate change is crucial for conservation management, especially when their conservation status is critical or unknown.